Demography and incidence of peripheral nerve injury in extremity trauma - Pandey, Suresh; Bidari, Suraj (Nepal Orthopaedic Association Journal, 2020)
INTRODUCTION: Peripheral Nerve Injury can have significant long term morbidity. They are common injury in the extremity trauma but demographic data and incidence vary. This study aimed to analyze the demographic data and incidence of Peripheral Nerve Injury in the upper and lower limb trauma.METHODS: This was a retrospective cross section study of the medical records of all the extremity injury admitted in the orthopaedic inpatient with or without peripheral nerve injury in the period of one year from January 1, 2019 to December 31, 2019 in the tertiary care teaching hospital. Details of the demographic data such as age, sex, and injury details (mode of injury, complete diagnosis, nerve involved, closed or open injury, associated injury) were entered in the data sheet and results were analyzed along with possible associations.RESULT: There were total of 4.04% (n=31) cases of peripheral nerve injury out of total 766 upper and lower limb traumatic inpatients. Mean age of the patients with Peripheral Nerve Injury was 24.58 years (range 5-50) with male predominace. Radial nerve injury was most common followed by median and ulnar nerve. Peripheral Nerve Injury was more common in upper limb trauma, open injury, Road Traffic Accident and associated vascular injury.CONCLUSION: Incidence of Peripheral Nerve Injury was 4.04% of all the extremity injured inpatients in the orthopaedics. There was predilection of male sex, younger age group and upper limb injury. Radial nerve was the most commonly injured nerve and there was significant association of Peripheral Nerve Injury with open injury and vascular injury.